Real-world experience of gene therapy with onasemnogene-abeparvovec (Zolgensma®) for patients with SMA-type1 in UK. Issue 9 (12th August 2022) - Gowda, Vasantha; Wraige, Elizabeth; Ong, Min; Atherton, Mark; Majumdar, Anirban; Marco, Silvia Sanchez; Hughes, Imelda; Mccullagh, Gary; Muntoni, Francesco; Jungbluth, Heinz; ,
Abstract : Retrospective review of referrals to the National-Multidisciplinary-Team (NMDT) in England (& Wales), and of the clinical records of SMAtype1 patients included for Zolgensma® therapy in the UK. Data was available for 42 patients: 13, 12, 10, 6, 1 from Evelina-London, Sheffield, Bristol, Manchester and Belfast centres respectively. Patients' age ranged from 2-months to 46-months and weights from 4.44kg to 13.5kg. Post-Zolgensma-infusion monitoring: Most patients had asymptomatic thrombocytopaenia in week-1, resolving by week-2. No thrombotic microangiopathy was reported. Majority developed transient transaminitis with mild/moderate elevation of AST/ALT. Some had more severe/prolonged transaminitis – Liver ultrasound, coagulation-studies and clinical examination remained normal: 11 (weight>7.5kg) had ALT-peaks of >100 IU/L; 22 (15/22 weighed >7.5kg) had AST-peaks of >100 IU/L – good response seen to doubling Prednisolone, where indicated. Echocardiograms remained normal in patients with elevated Troponin-I levels; 4 had levels >100ng/l, prednisolone doubled in one, with good response. 13/42 needed doubling of Prednisolone; 12/13 had weight >7.5kg. CHOP-INTEND scores post gene-therapy were available for 22/42. Scores improved in all patients except one (difficult assessment). Improvement ranged from 2-24 points. Conclusion: All patients tolerated the Zolgensma®-therapy well and have recovered well from any transient issues. No persistent complications from gene-therapy or steroid-cover were reported.